2015
DOI: 10.1097/brs.0000000000000829
|View full text |Cite
|
Sign up to set email alerts
|

Letter

Abstract: d e Mello FM, et al 1 reported that axial gout was not rare, and the incidence in their study of patients with gout was up to 29%. The proportion of axial gout in patients with gout would be really so high? We think that the answer might not be particularly determined.First, although several previous studies have confi rmed that computed tomography was useful in preliminary diagnosis of spinal gout, the "gold standard" remains histopathological examination. 2-5 Second, the mean age of patients enrolled in thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…Although the demonstration of MSU crystals in tissue samples is the gold standard for diagnosing gout, previous studies suggested that CT is a useful imaging modality in the initial diagnosis of axial gout ( 5 , 7 10 , 18 ). Hongli et al raised a question on whether the gout-suggestive features on CT are specific for axial gout or gouty arthritis, especially for abnormal bony neoformations of the facet joints and intervertebral disk ( 22 ). Thus, these abnormal bony neoformations were not considered as being a suggestive feature of axial gout in the CT in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Although the demonstration of MSU crystals in tissue samples is the gold standard for diagnosing gout, previous studies suggested that CT is a useful imaging modality in the initial diagnosis of axial gout ( 5 , 7 10 , 18 ). Hongli et al raised a question on whether the gout-suggestive features on CT are specific for axial gout or gouty arthritis, especially for abnormal bony neoformations of the facet joints and intervertebral disk ( 22 ). Thus, these abnormal bony neoformations were not considered as being a suggestive feature of axial gout in the CT in the present study.…”
Section: Discussionmentioning
confidence: 99%